Esterification of oleic acid with ethanol using tungstated zirconia : kinetic and modelling study - M. Ilyas, Zubir (2009)
The esterification of free fatty acids (FFA) mostly found in vegetable oils with ethanol using solid acid catalyst is one of promising method to convert FFA into Fatty Acid Ethyl Ester (FAEE) that is an alternative to replace fossil fuel as energy source mostly in transportation sector. The present study aimed to determine the optimum or best operating condition for the production of FAEE by esterification of oleic acid and ethanol with tungstated zirconia used as solid acid catalyst. Tungstated zirconia used must be activated at 800°C for it functions at the best state by providing most active site for the reaction occur besides providing alternative route that lower than activation energy for reaction to occur. Kinetic model has been developed after the optimum operating condition is determined. From the scope of study, the optimum operating condition of oleic acid esterification can be achieved at 50°C, 1.5 g tungstated zirconia solid catalyst and 5:1 ethanol to oleic acid molar ratio that brings 24.24% oleic acid conversion. Kinetic model used is pseudohomogeneous and from the model, activation energy for esterification which is 9.72 kJ/mol can be determined.